Comportamento da carga de treinamento, recuperaçao e bem-estar em atletas profissionais de voleibol em semanas com e sem jogos - Martins Brandao, Fernanda (2018)
The aim of this study was to compare the internal training load, recovery state and the well-being of volleyball professional athletes, according to the number of matches during the week. The recovery was quantified with TQR Scale, the training load with sRPE and the well-being with QBE Scale. The ANOVA was applied for repeated measures in order to compare the values of Total weekly training load, the delta of Total Quality Recovery (DTQR) and the delta of the quality of well-being (DQBE),. There was no significant difference among the training load and the frequency of weekly games, but the effect size was very high when it was compared to the difference between one and two weekly games, as well as any and two games in a week. There were differences on the DTQR between weeks without games and with two games, as well as weeks with one and two matches. The DQBE was different for weeks in which there was no game and those with matches, regardless of the frequency. It was concluded that, even if there is no variation of loads in different weekly frequency of matches, the athletes' recovery and well-being change.